Response to 'Views of oral antibiotics and advice seeking about acne: a qualitative study of online discussion forums' based on evidence obtained from The Acne Priority Setting Partnership. (24th January 2019) - Horton, E.; Lee, N.; Layton, A.M.; Eady, E.A.
Abstract : Linked Article : Santer et al. Br J Dermatol 2017; 177 :751–7 .